The JIDA conference: Teaching practice as research - Berta Bardí-Milà; Daniel García-Escudero (OmniaScience, 2018)
The Workshop on Educational Innovation in Architecture (JIDA) promotes reflection and debate among the faculty of the different schools of architecture. The communications presented in the five editions held so far (2013-2017) can be considered a "living archive" of the teaching practices of more than thirty Spanish and twenty foreign universities. This material is extremely helpful for improving the education of architects and to lay the foundations for research into the instructional scenario in this discipline. With this purpose in mind, work is being done on a constellation of terms related to pedagogical practices, which is intended to conceptualize the diversity of strategies and methodologies presented these years at the conference. This sample of teaching experiences is a base upon which to consider the current situation of schools of architecture and to ask ourselves: what will training be like for architects 20 years from now?